Contrast-Enhanced MR Angiography at 3T in the Evaluation of Intracranial Aneurysms: A Comparison with Time-of-Flight MR Angiography - Nael, K. (AJNR Am J Neuroradiol, 2006)
SUMMARY: The combination of 3T and parallel-acquisition techniques holds promise for improved performance of contrast-enhanced MR angiography (MRA), in terms of speed, spatial resolution, and coverage. We present a comparison of 2 MRA techniques, including time-of-flight (TOF) and contrast-enhanced MRA, for detection and evaluation of intracranial aneurysms. Our results show that contrast-enhanced MRA with highly accelerated parallel acquisition at 3T does not have the known drawbacks of TOF-MRA techniques, including prolonged acquisition time, spin saturation, and flow-related artifacts, with comparable aneurysm characterization.